ERGONOMIC ANALYSIS OF MUSCULOSKELETAL PROBLEM AND FATIGUE AMONG CATERING WORKERS - Devi Prabhasanti (Bajang Institute, 2021)
Musculoskeletal disorders (MSD) are condition including muscle which exaggerated by stress and repetitive or static position for a long time, meanwhile fatigue is body protection mechanism. Those two problems had been known as risk to workers and affected their productivity. An ergonomic analyzed included task, organization and environment needed to decrease and prevent of work musculoskeletal problem and fatigue among the workers, because those will affect their focus, productivity, worsen if there any injury and disability. This observational study aims to evaluate ergonomic analysis to musculoskeletal problem and fatigue to catering workers industry at Denpasar Bali. Samples of this study were catering workers, observes done by writer based on ergonomic analysis in aspect task, organization and environment. Musculoskeletal problem measured by Nordic Body Map (NBM) and fatigue assessed used questionnaire by Japan Association Industrial Health (JAIH). Data analysis used SPSS. Due to condition, in the catering industry their task divided good, but for the break time of workers too short and the environment not find ergonomic standard in the lighting, noise and safety equipment. Parametric and non-parametric test musculoskeletal problem and fatigue pre work and after work among the workers shown significant difference (p<0,05). Therefore, ergonomic standard for the environment in the catering work industry need to improve for prevent of musculoskeletal problem and fatigue among catering workers.